Sponges With Microbial Symbionts Transform Dissolved Organic Matter and Take Up Organohalides - Olinger, Lauren K.; Strangman, Wendy K.; McMurray, Steven E.; Pawlik, Joseph R. (Frontiers in Marine Science, 2021)
Seawater dissolved organic matter (DOM) is a large reservoir of carbon composed of a complex and poorly characterized mixture of molecules. Sponges have long been known to consume dissolved organic carbon (DOC) from this mixture, but the role of microbial sponge symbionts in this process is complex, and the molecules involved remain largely unknown. In order to better understand how sponge processing changes seawater DOM, we used untargeted metabolomics to characterize DOM in samples of incurrent and excurrent seawater taken from sponges on the fore-reef off Carrie Bow Cay, Belize, over 2 years. We collected samples from three sponge species each with either high or low microbial abundance (HMA, LMA) to explore the relationship between symbiont abundance and DOM alterations. Analyses revealed that sponges took up metabolites and changed the composition of seawater DOM, but only for the three HMA species, and none of the LMA species, implicating microbial symbionts in this uptake. Using a new mass spectra classification tool, we found that putative compositions of features depleted in the excurrent samples of HMA sponges were similar in both years and were dominated by organic acids and derivatives (74%) and organic nitrogen compounds (19%). Interestingly, HMA sponges also took up halogenated compounds (containing chlorine or bromine), providing evidence of a previously unknown mechanism of halide cycling. The metabolites taken up by HMA sponges may be used as a food source or as building blocks of chemical defenses, selective advantages that may have guided the evolution of microbial symbioses in sponges.